(untitled) (Proceedings of International Educators Conference, 2024)
In recent years, advancements in educational technologies have significantly enhanced simulation and imitation models, facilitating the application of advanced methods in teaching chemistry. These approaches help students intuitively comprehend chemical concepts, develop their learning abilities, and increase their interest in the educational process. Simulation models also hold significant pedagogical importance, fostering students’ critical thinking and practical skills. This article analyzes how simulation models enhance educational effectiveness, drawing upon the work of leading researchers and educational technologies. Additionally, it highlights how this methodological approach creates innovative opportunities within the educational process.